Correlation between individual thigh muscle volume and grip strength in relation to sarcopenia with automated muscle segmentation. - Hyeon Su Kim; Shinjune Kim; Hyunbin Kim; Yonghan Cha; Jung-Taek Kim; Jin-Woo Kim; Yong-Chan Ha; Jun-Il Yoo (PLoS ONE)
Introduction Grip strength serves as a significant marker for diagnosing and assessing sarcopenia, particularly in elderly populations. The study aims to explore the relationship between individual thigh muscle volumes and grip strength, leveraging advanced AI-based UNETR segmentation techniques for accurate muscle volume assessment. Methods The study included 49 participants from a cohort of 478 patients diagnosed with hip fractures at Gyeongsang National University Hospital. We recorded Grip strength and height and utilized UNETR-based segmentation techniques on CT scans, to calculate individual thigh muscle volumes. Point-biserial correlation was employed to explore the relationship between sarcopenia and thigh muscle volumes. The research also included a quantile analysis of grip strength. Results Our findings revealed a strong statistical significance in specific thigh muscles like Rectus femoris, Vastus lateralis, and Vastus intermedius, particularly in males, in relation to sarcopenia. The male cohort displayed a trend where higher thigh muscle volumes correlated with better grip strengths. Meanwhile no such relationship was found within the female group. Conclusion The findings indicate that stronger grip strength correlates with larger thigh muscles in males but not in females, with specific muscles like the Rectus femoris and Vastus lateralis linked to sarcopenia in men only. The study's small sample size calls for further research with more diverse and gender-balanced groups to verify these results.